Clinical Outcomes in Patients with Cervical Spondylotic Myelopathy Treated with French door Laminoplasty - Thapa, Bishnu Babu; Pratap Shah, Rajesh; Maharjan, Dipendra (Medical Journal of Shree Birendra Hospital, 2023)
Introduction: Cervical spondylotic myelopathy (CSM) is a condition that results from cervical stenosis. The clinical manifestation of CSM are paresthesia of extremities, loss of motor functions, difficulty in walking and in severe cases bowel and bladder dysfunction. Mostly CSM is treated with surgical methods. In case of single level involvement, anterior surgery is commonly done and preferred posterior surgery for multilevel involvement. Among all posterior techniques, laminoplasty is one of the most popular ones. The study aims to assess the clinical outcomes of French door Laminoplasty in CSM. Methods: We retrospectively analysed the patients hospital record and radiographs who were operated with French door laminoplasty for cervical spondylotic myelopathy. We analysed pre and post operative mJOA score, axial neck pain and cervical lordosis. The data were analysed with SPSS version 20. Results: A total of 30 patients were evaluated. Majority of patients were males (27). All the patients pre and postop cervical lordosis measured and there is maintained cervical lordosis postoperatively. The mJOA score improved from 9.83 ± 1.82 to 14.27 ± 1.28 postoperatively at one year. Mean axial pain improved from 4.1 ± 1.19 to 1.7 ± 0.651 postoperatively. Conclusions: There is improved clinical outcome of cervical spondylotic myelopathy patients after French door laminoplasty surgery.